2016
DOI: 10.1097/aap.0000000000000495
|View full text |Cite|
|
Sign up to set email alerts
|

Quadratus Lumborum Block Versus Transversus Abdominis Plane Block for Postoperative Pain After Cesarean Delivery

Abstract: The quadratus lumborum block was more effective in reducing morphine consumption and demands than transversus abdominis plane blocks after cesarean section. This effect was observed up to 48 hours postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
271
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(313 citation statements)
references
References 18 publications
10
271
2
4
Order By: Relevance
“…Conversely, the block within the QLM revealed the spread of the contrast towards the paravertebral space between Th4-L1 spaces [10,13,23]. The aim of our study was to confirm what Blanco indicated in 2007, that a new concept of the block of the abdominal wall of the inhibitory effect of somatic and visceral pain, the so called paravertebral block component, was beneficial [14,15]. There were no published studies evaluating the effectiveness of the QLB I and post-cesarean section until 2014, when the protocol of the clinical trial presented here was developed.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Conversely, the block within the QLM revealed the spread of the contrast towards the paravertebral space between Th4-L1 spaces [10,13,23]. The aim of our study was to confirm what Blanco indicated in 2007, that a new concept of the block of the abdominal wall of the inhibitory effect of somatic and visceral pain, the so called paravertebral block component, was beneficial [14,15]. There were no published studies evaluating the effectiveness of the QLB I and post-cesarean section until 2014, when the protocol of the clinical trial presented here was developed.…”
Section: Discussionsupporting
confidence: 68%
“…There were no published studies evaluating the effectiveness of the QLB I and post-cesarean section until 2014, when the protocol of the clinical trial presented here was developed. According to various studies published since 2015, the QLB and its variants are an effective analgesic tool compared with the TAPB due to the absence of the paravertebral component; a smaller scope of activities; and the possibility of fewer complications [15,16,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some blocks (such as Pecs and quadratus lumborum blocks) have undergone randomized investigation with trials of variable quality (Jadad scores raging from 2 to 4). [53][54][55][59][60][61]64,67,74 Other blocks (such as the pecto-intercostal fascial plane blocks) are still searching for a legitimate application. 65,66 A few, such as US-guided thyroid capsular sheath blocks, may never find a clinical role because of sheer interference with the surgical field.…”
Section: Limitations Of Ultrasound Guidancementioning
confidence: 99%
“…The anterior QL block can also provide analgesia from T10 to L3 [76]. A study by Blanco et al [77,78] …”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%